Educandy Educational Game-Based TGT Learning Model: Students' Interests and Learning Achievement - Meilanisa Meilanisa; Makmur Makmur; Muh. Agil Amin (Education and Talent Development Center Indonesia (ETDC Indonesia), 2026)
This research was motivated by the low interest and learning achievement of students in the Aqidah Akhlak subject, which remained dominated by conventional, teacher-centered methods, leading to passive and unenthusiastic student engagement. This study aimed to implement and evaluate the effectiveness of the Teams Games Tournament (TGT) learning model integrated with the Educandy educational game in improving the interest and learning outcomes of Class VIII A students at MTs Satu Atap Datok Sulaiman Palopo. Using a Classroom Action Research (CAR) approach across two cycles—comprising planning, implementation, observation, and reflection—this study involved 29 students as subjects. Data was collected through observations, questionnaires, and learning outcome tests, then analyzed using descriptive quantitative and qualitative techniques. The findings demonstrate that the implementation of the Educandy-based TGT model successfully transformed the learning process into a more interactive, enjoyable, and competitive experience. Empirically, the synergy between teamwork and digital game elements significantly improved both effective and cognitive dimensions. Student learning interest increased from an average of 76.3% (Good) in Cycle I to 91.1% (Very Good) in Cycle II. Similarly, cognitive learning outcomes showed a drastic improvement; the average score rose from 74.13 (48.27% completion) in Cycle I to 90.00 (96.55% completion) in Cycle II. These findings show that using digital educational games in a cooperative way greatly boosts student interest and participation, making it very effective for teaching religious topics, especially good manners.